English Teaching and Learning Problems in The General Program of Bangbowitthayakhom School, Thailand - Supasan, Haranee (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This research was conducted at Bangbowitthayakhom School, Thailand, and aimed to investigate teachers and students’ English language teaching and learning problems in the General Program as well as find feasible measures to solve the problems. A mixed research design was used to process the data collection and data analysis. There were three instruments applied in this study. (1) the 5 Likert scale questionnaire was administered to 275 students in the General Program by randomly selected one room per one level ranging from Mathayom 1-.6 and (2) the 5 Likert scale questionnaire was administered to 24 teachers from the Foreign Language Department. Additionally, (3) the semi-structured interview was performed by four teachers. The data was analyzed by percentages, means, and standard deviation of the questionnaire. The data from the interview was transcribed, categorized, and described. The study’s results revealed that students agreed at a high level with the problems about themselves. The list of the top three statements was: (1) students lack opportunities of using English outside the class, (2) students think in Thai first before they translate it into English, as well as (3) students want to study with native speakers of English more than Thai teacher respectively. The results from teachers’ questionnaires showed that teachers agreed on a high level with problems involving students too. They mostly agreed that students thought in Thai first before they translated it into English. However, problems involving curricula and textbooks and other factors related to English language teaching were agreed to a moderate level. Lastly, problems involving teachers and assessment were at a low level. Despite this, teachers found feasible measures: game-based learning, and the flipped classroom method, and used student-centered approach to successfully solve problems. The teachers also recommend that the program should incorporate more opportunities for teacher development seminars. They believed these seminars would keep teachers up to date on the latest education techniques being used.